Fish eating behavior among toddlers - Khusnul Khotimah; Yuli Trisnawati (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Fish is a major source of essential nutrients, including omega-3 fatty acids, vitamin D, iodine, and high-quality protein, which are vital for healthy growth and development during childhood. The World Health Organization (WHO) and other international organizations recommend that infants begin consuming fish between 6 and 9 months of age and continue to consume it regularly once a week. However, there is slight variation among guidelines regarding the quantity and frequency of fish consumption for children. Based on data from the Food and Agriculture Organization (FAO), the average global per capita fish consumption tends to increase, with the latest data estimates showing around 20.5 kilograms per person per year. Global consumption of fish, excluding algae, has increased significantly. Purpose: to determine the fish-eating behavior of toddlers. Method: This study is a quantitative descriptive observational study with a cross-sectional design conducted in Adisara Village in November 2025. This study was conducted in the Adisara Village area as a fish processing center in the Banyumas region because some residents work as fish managers and sea fish sellers who fill some markets in the Banyumas Regency area. The population was all mothers of toddlers in Adisara Village totaling 152 people. Results: While sampling was carried out using a cluster sampling approach obtained a sample of 45 people. So based on the results of the questionnaire, it was obtained that the behavior of eating fish in toddlers tends to be less, namely in the frequency question section 1-3 times and a week and one of them is also supported by the lack of information about potential allergens and concerns about contaminants. This is also supported by the fact that the majority of mothers choose to introduce fish to toddlers after 12 months of age, partly due to the informational concerns discussed above. Conclusio: Therefore, specific education on this issue is needed to increase the quantity of fish consumed by toddlers.